Constrictive Pericarditis Leading to Cardiac Cirrhosis: A Rare Cause of Chronic Liver Disease - Subha, Nahid e; Akter, Sharmin; Sabiha, Aysha; Hasan, Md Shariful; Bayes, Farhana; Mazumder, Wahiduzzaman (Dhaka Shishu (Children) Hospital Journal, 2021)
Abstract not available DS (Child) H J 2020; 36(1) : 71-74